Analysis of the efficiency of the activated sludge system by microscopy (Revista Brasileira de Contabilidade e Gestão, 2016)
The industry needs a lot of water in its production process and with this the generation of effluents is produced. One of the most widely used ways to treat this wastewater is biological treatment using activated sludge. For this system to meet expectations, it needs good debugging, that is, it must be efficient. Thus, the article aims to analyze the efficiency of the activated sludge system through microscopy, identifying the microorganisms present in a sludge sample collected on November 12, 2014 in a textile industry in Alto-Vale do Itajaí. After microscopy, the data was analyzed and a diagnosis of treatment problems was obtained.
Keywords: sludge; microorganisms; microscopy; wastewater treatment